Hörformen V : Begegnungen mit Flandern und Wallonien in Berlin. - Künstlerhaus Bethanien, Berlin (Berlin : Künstlerhaus Bethanien, 1986)
De Mey, Thierry ; Descheemaeker, Dirk ; Sleichim, Eric ; Vermeersch, Peter ; Deppe, François ; Hus, Walter ; Grosskopf, Erhard ; Pousseur, Henri ; Stockhausen, Karlheinz ; Goeyvaerts, Karel ; Goethals, Lucien ; etc.
Hörformen V : Begegnungen mit Flandern und Wallonien in Berlin : Konzert 1: Maximalist, 17. April 1986 / Konzert 2, 19. April 1986 / Konzert 3, 20. April 1986, Künstlerhaus Bethanien, Berlin
boek